2009
DOI: 10.1016/j.juro.2009.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Efficacy of the Highly Selective α 1A -Adrenoceptor Antagonist Silodosin in Men With Signs and Symptoms of Benign Prostatic Hyperplasia: Pooled Results of 2 Phase 3 Studies

Abstract: Treatment with silodosin produced rapid improvement in urinary symptoms that was sustained for 12 weeks. Silodosin was well tolerated with a low incidence of orthostatic hypotension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
109
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(122 citation statements)
references
References 14 publications
11
109
2
Order By: Relevance
“…In a United States clinical study, Marks et al [11] reported the efficacy and safety of silodosin 8 mg (once daily) for the treatment of BPH in two randomized placebo-controlled phase 3 studies. Of 923 patients with a mean age of 65 years, 466 received silodosin 8 mg and 457 were given placebo for 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…In a United States clinical study, Marks et al [11] reported the efficacy and safety of silodosin 8 mg (once daily) for the treatment of BPH in two randomized placebo-controlled phase 3 studies. Of 923 patients with a mean age of 65 years, 466 received silodosin 8 mg and 457 were given placebo for 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…However, few patients receiving silodosin (2.8%) discontinued because of retrograde ejaculation. Proportions of patients with treatment-emergent orthostatic hypotension were similar for silodosin (2.6%) and placebo (1.5%) 28. It has been reported that tamsulosin can also cause abnormal ejaculation.…”
Section: Safety and Tolerability Of Silodosinmentioning
confidence: 73%
“…It has been reported that α 1A -AR blockade relieves bladder outlet obstruction, while the blocking the α 1D -AR is believed to alleviate storage symptoms due to detrusor overactivity 1. However, silodosin (KMD-3213 or [(-)-1-(3-hydroxypropyl)-5-[(2R)-2-({2-[2-(2,2,2trifluoroethoxy)phenoxy]ethyl} amino) propyl]-2,3-dihydro-1H-indole-7-carboxamide]), a new α 1A -AR selective antagonist, has been reported to be effective for both storage and voiding symptoms in BPH patients 27,28. This suggests that the α 1A -AR alone is responsible for both storage and voiding symptoms in LUTS/BPH.…”
Section: Introductionmentioning
confidence: 99%
“…Total symptom score improved by 30–40% and Qmax by 16–25% [17]. The clinical efficacy of silodosin at the dose of 8 mg for the treatment of LUTS/BPH has been evaluated by two placebo-controlled phase III studies, one non-inferiority study of silodosin vs tamsulosin and one of superiority vs placebo, and one randomized, double-blind study vs tamsulosin [16, 1821]. Results from phase III studies demonstrated a mean decrease of total IPSS in patients receiving silodosin varying from −6.4 to −10.6.…”
Section: Clinical Efficacy Profilementioning
confidence: 99%
“…Results from phase III studies demonstrated a mean decrease of total IPSS in patients receiving silodosin varying from −6.4 to −10.6. The mean decrease of voiding IPSS and storage IPSS vary from −4.0 to −7.1 and from −2.3 to −3.5, respectively [16, 1821]. Chapple et al compared silodosin with tamsulosin and placebo in a placebo-controlled active and parallel group design [16].…”
Section: Clinical Efficacy Profilementioning
confidence: 99%